Interfering with pak4 Protein Expression Affects Osteosarcoma Cell Proliferation and Migration. (30th December 2021) - Fu, Yuxin; Fang, Lun; Yin, Qipu; Wu, Qi; Sui, Wei; Sun, Ying; Zhao, Xindi; Wu, Yadi; Zhou, Lu
Abstract : Purpose . A number of studies have discovered various roles of PAK4 in human tumors, including osteosarcoma. However, the exact role of PAK4 in osteosarcoma and its mechanism have yet to be determined. Therefore, this study focused on interrogating the PAK4 effect on the proliferation and migration ability of osteosarcoma and its underlying mechanisms. Materials and Methods . Western blot and QRT-PCR were utilized to quantify the PAK4 relative protein and mRNA levels. To measure cellular viability and mobility, the MTT and wound-healing assays were preferred. Results . With the adenovirus-mediated overexpression of PAK4, the proliferation and migration of U2-OS and MG-63 osteosarcoma cells were stimulated. Furthermore, a liposome-mediated knockout of PAK4 will inhibit osteosarcoma cells from proliferating. In terms of mechanism, we observed the positive correlation of PAK4 expression with expression of P21, CyclinD1, CyclinE1, CDK2, and CDK6, which drives G0/G1 to the G2/M phase transition. PAK4 can also activate Erk expression in OS cells and induce EMT. Conclusion . Interfering with PAK4 protein expression has been shown to affect osteosarcoma proliferation and migration.